Prolegomena mathematica : from Apollonius of Perga to late Neoplatonism : with an appendix on Pappus and the history of Platonism - Mansfeld, Jaap. (Philosophia Antiqua, 1998)
This is the first study to deal with the history of Greek mathematics - starting with Appollonius and including astronomy - as part of the history of literary culture. It attempts to find out how mathematical works were presented by original authors (e.g. Ptolemy), and introduced and explained by commentators (e.g. Pappus who is at the centre of this enquiry, Eutocius, and prolegomena by late Anonymi). The manner in which mathematical treatises were presented and studied is entirely comparable to that practised in e.g. philosophy, medicine, biblical and literary studies (see the author's Prolegomena , ( Brill , 1994)). Discussion of introductory issues is a standard feature, and in mathematics the development from the implicitly expressed to the explicitly expressed and from there to scholastic routine is the same as in these other fields.